Attitudes of the police candidates according to football supporter fanaticism scale - Taner Tunc; Fatih Karakas; Soner Cankaya; M. Yalçin Tasmekteplıgıl (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to determine the attitudes of the students of the Police Vocational High School about being a supporter. Football Supporter Fanaticism Scale (FSFS) was used on a total of 980 students. The coefficient of consistency was found to be 0.877 for FSFS. Factor analysis was made to test the structural validity of the study. The results of the study revealed that 1.6 % of the male students were fanatic, 11 % were supporters and 87.4% were spectator while 0.4 % of the female students were fanatic, 7.7 % were supporters and 91.9 % were spectator. These results show that the future the police regards sport organizations as fun and they do not have any extreme attitudes. In order to prevent violence, such studies should occasionally be done on police department and sports club supporter groups and the tendency of individuals for violence should be assessed.